Inhibitory proproteinowej konwertazy subtylizyny/keksyny 9 nowym, przełomowym narzędziem terapeutycznym w leczeniu dyslipidemii = Proprotein convertase subtilisin/kexin type 9 inhibitors are a new, groundbreaking therapeutic tool in the treatment of dyslipidemia - Łukasz Wołowiec; Joanna Banach; Daniel Rogowicz; Magdalena Grochowska; Walery Zukow; Władysław Sinkiewicz (Kazimierz Wielki University, 2016)
Wołowiec Łukasz, Banach Joanna, Rogowicz Daniel, Grochowska Magdalena, Zukow Walery, Sinkiewicz Władysław. Inhibitory proproteinowej konwertazy subtylizyny/keksyny 9 nowym, przełomowym narzędziem terapeutycznym w leczeniu dyslipidemii = Proprotein convertase subtilisin/kexin type 9 inhibitors are a new, groundbreaking therapeutic tool in the treatment of dyslipidemia. Journal of Education, Health and Sport. 2016;6(7):525-539. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58882 http://ojs.ukw.edu.pl/index.php/johs/article/view/3716       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016.     Inhibitory proproteinowej konwertazy subtylizyny/keksyny 9 nowym, przełomowym narzędziem terapeutycznym w leczeniu dyslipidemii Proprotein convertase subtilisin/kexin type 9 inhibitors are a new, groundbreaking therapeutic tool in the treatment of dyslipidemia   Łukasz Wołowiec1, Joanna Banach1, Daniel Rogowicz1, Magdalena Grochowska1, Walery Zukow2, Władysław Sinkiewicz1   1 II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2 Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy       Streszczenie Aktualnie najczęściej stosowaną grupą leków hipolipemizujących są statyny, które skutecznie redukują ryzyko niekorzystnych zdarzeń sercowo-naczyniowych w profilaktyce zarówno pierwotnej, jak i wtórnej. Stosowanie statyn może się jednak wiązać z nietolerancją tej grupy leków i występowaniem działań niepożądanych, których częstość zwiększa się w przypadku terapii skojarzonej z innymi lekami hipolipemizującymi. Ponadto u kilku procent chorych pomimo zastosowania skojarzonej terapii lekami hipolipemizującymi, nie udaje się osiągnąć docelowych wartości stężenia cholesterolu LDL (z ang. low-density lipoprotein - LDL, LDL-C). Nowa grupa leków - inhibitory proproteinowej konwertazy subtylizyny/keksyny 9 (PCSK9), które regulują stężenie receptora dla LDL-C, wydają się być nowym, skutecznym narzędziem terapeutycznym, stosowanym celem osiągnięcia docelowych wartości cholesterolu LDL. Celem pracy było przedstawienie metabolizmu cholesterolu w organizmie człowieka, znaczenia skutecznej terapii zaburzeń gospodarki lipidowej, aktualnego stanu wiedzy na temat białka PCSK9 i jego inhibitorów. Opisano wyniki najważniejszych badań klinicznych z inhibitorami PCSK-9.   Słowa kluczowe: cholesterol, proproteinowa konwertaza białkowa subtylizyna/keksyna typu 9 (PCSK9), inhibitory PCSK9.     Abstract Statins are currently the most frequenly used  group of lipid-lowering drugs. This group of drugs can effectively reduce the risk of adverse cardiovascular diseases in both primary and secondary prevention, however,  their impementation may lead to intolerance and other side effects, the frequency of which increases in the case of a combined therapy with other lipid-lowering drugs. Additionally, in spite of the therapy a litte percenatge of the patients still cannot reach the target concentartion of LDL cholesterol. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors (a  new class of drugs  that regulate the concentration of LDL cholesterol receptor) seem to be a  new and effective therapeutic tool used to reach the target level of LDL cholesterol. The aim of the study was to present the cholesterol metabolism in human body, the significance of an effective therapy for lipid disorders as well as the current knowledge of the PCSK9 protein and its inhibitors.   Key words: cholesterol, proprotein convertase subtilisin/kexin type (PCSK9), PCSK9 inhibitors.